2011
DOI: 10.1017/s1092852912000363
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Dimensional Approach and BDNF in Unmedicated Obsessive-Compulsive Patients: An Exploratory Study

Abstract: There were no sociodemographic differences between the groups. The standard error of mean serum BDNF levels were reduced in unmedicated OCD patients (0.47+0.038) when compared to healthy controls (0.75+0.060) (P<.001). The patients with the presence of sex/religion obsessive-compulsive symptoms (OCS) dimension (P=.002), with chronic course of OCS (P=.022) and the presence of lifetime major depression (P=.016) and social anxiety (P=.030) presented higher levels of BDNF than OCD patients without those features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
2
21
1
Order By: Relevance
“…Contrary to some studies reporting negative correlations between BDNF levels and illness duration [72], and age in schizophrenia, which may indicate disease progression [30], we found no correlations similar to a previous study [74]. We also found no correlation with YBOCS scores [14,45], contrary to negative correlation between BDNF levels and functioning [22], and positive correlations between GDNF levels and severity of ordering/washing symptoms which may be related to disturbed dopaminergic activity [22]. Since GDNF is a trophic factor for dopaminergic neurons [29], a negative correlation between insight scores may highlight some dopaminergic activity in OCD patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to some studies reporting negative correlations between BDNF levels and illness duration [72], and age in schizophrenia, which may indicate disease progression [30], we found no correlations similar to a previous study [74]. We also found no correlation with YBOCS scores [14,45], contrary to negative correlation between BDNF levels and functioning [22], and positive correlations between GDNF levels and severity of ordering/washing symptoms which may be related to disturbed dopaminergic activity [22]. Since GDNF is a trophic factor for dopaminergic neurons [29], a negative correlation between insight scores may highlight some dopaminergic activity in OCD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Disturbed plasticity may also be involved in the pathogenesis of OCD [22]. Reduced BDNF levels [14,22] regardless of drug treatment [73] and comorbid depressive disorder [45], but unchanged GDNF levels [22] are in line with our findings. Dysregulation of glutamatergic system is unclear in OCD [59].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our previous work, we examined BDNF plasma levels in OCD, finding that BDNF plasma levels in drug-naïve OCD patients were lower than those in healthy people, but were not lower than those in drug-treated OCD patients (Wang et al, 2011). Other studies found that BDNF serum level was lower in OCD, and serum level was related to some special dimensions (Dos Santos et al, 2011) . Study about GAD found that BDNF plasma levels significantly increased after duloxetine treatment for 15 weeks (Ball et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…So in this study, we did not divided patients into different subgroups according to their medication states. The only other two studies about BDNF levels in OCD patients reported that OCD patients showed lower BDNF serum levels compared to healthy controls (Dos Santos et al, 2011;Maina et al, 2010). A recent meta-analysis found that the change of BDNF levels was not consistent across various anxiety disorders and the totally decreased trend among anxiety disorders might largely be explained by the significantly lowered BDNF levels found in OCD (Suliman et al, 2013).…”
mentioning
confidence: 99%